(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we define essential fuzzy ideals of semirings and investigate some properties of them. We give some properties of essential ideals and essential fuzzy ideals. Moreover, we show relationships between essential ideals and essential fuzzy ideals.